2008
DOI: 10.1080/08820530802505997
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Area and Retinal Area in Amblyopia

Abstract: The increase in the receptor area may be an explanation for diminished acuity and impaired visual function in amblyopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(35 reference statements)
1
7
0
1
Order By: Relevance
“…Nonetheless, in comparing our findings with those from adult studies, we found that our distributions are similar to most3 15 19 20 but not all16–18 22 reports. For example, the Beijing Eye Study3 reported a mean optic-disc area of 2.38 mm 2 from planimetry of optic disc photographs of 781 Chinese subjects, similar to our findings, while Budde et al 22 reported a mean disc area of 3.09 mm 2 in a sample of 193 German subjects, substantially larger than in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, in comparing our findings with those from adult studies, we found that our distributions are similar to most3 15 19 20 but not all16–18 22 reports. For example, the Beijing Eye Study3 reported a mean optic-disc area of 2.38 mm 2 from planimetry of optic disc photographs of 781 Chinese subjects, similar to our findings, while Budde et al 22 reported a mean disc area of 3.09 mm 2 in a sample of 193 German subjects, substantially larger than in our study.…”
Section: Discussionsupporting
confidence: 73%
“…However, definitive evidence that anisometropia universally precedes development of the amblyopia is lacking, and the simplicity of this cause and effect relationship continues to be challenged (Almeder et al, 1990; Barrett et al, 2005; Lempert, 2000, 2003, 2004, 2008a, 2008b; Lempert and Porter, 1998, Smith and Hung, 1999). In light of the general uncertainty about the aetiology of anisometropia and anisometropic amblyopia, an examination of the literature is timely as part of the continuing effort to refine approaches to vision screening and clinical care.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…In several photographic studies, Lempert has characterized the ON to be smaller in amblyopic than in sound fellow eyes, motivating his postulate that amblyopic eyes have decreased visual acuity due to ON hypoplasia and reduced innervation of retinal areas, resulting in enlarged retinal receptor fields 2-7. Lempert theorizes that decreased vision in presumed amblyopic eyes is due to an asymmetric defect in neuro-retinal development due to a gestational insult.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of photographic studies,2-7 Lempert has asserted that eyes presumed amblyopic actually have abnormal appearing disks (“dysversion”), as well as abnormally small optic disks, axial length (AL), and an abnormally large ratio of AL to optic disk area (DA) compared to both the sound fellow eye and to normal controls. Lempert's claim of smaller optic disks in amblyopia is contradicted by several studies utilizing optical coherence tomography (OCT) or scanning laser polarimetry that failed to show a significant difference in optic nerve size or retinal nerve fiber layer (rNFL) thickness between amblyopic and control eyes 1, 12-17…”
Section: Introductionmentioning
confidence: 99%